Análise dos fatores críticos de sucesso na implementação de ERP cloud em PMEs: um estudo de caso em organizações brasileiras - Barbieri, Leonardo Moro (Universidade do Vale do Rio dos Sinos, 2023)
Digital transformation has changed business processes and operations for companies around the world. To remain competitive in a globalized market, companies need to adopt new technologies that can automate and drive the business forward. Therefore, the ERP Cloud has been a facilitator for Small and Medium Enterprises (SMEs) to have process controls and improve their performance at a cost compatible with the scarce resources they must invest. Therefore, this study aims to verify how the critical success factors (CSF) impact the implementation of ERP Cloud in Brazilian SMEs. This research was conducted through a case study with semi-structured interviews with five SMEs, and a total of ten interviews. The results indicate the CSF that impacts the implementation of ERP Cloud, classified according to the TOE framework (technology-organization-environment). All factors addressed in this study were considered by the interviewees as relevant, some receiving greater emphasis than others for the implementation to occur successfully. Among the factors that were highlighted are the security with which the data are stored in the service provider, the cost reduction due to the company not having the need to make initial investments in infrastructure, the expenses with maintenance, and the need to maintain a specialized internal team. Furthermore, the participation of top management proved to be a fundamental factor in the orchestration of the project, providing resources, facilitating communication, and team synergy. Finally, this study contributes to the literature by identifying two new CSF, which are the best practices made available by the standard implementation of the system, and the importance of process modeling for a successful implementation. In terms of practical contribution, this study helps companies and decision-makers who intend to implement ERP Cloud to understand which CSF should be monitored during the implementation process for the SME to achieve success.
Keywords: ERP Cloud; PME; Fatores críticos de sucesso; TOE framework; SME; Critical success factors; ACCNPQ::Ciências Sociais Aplicadas::Administração